The effects of beetroot juice supplementation on exercise economy, rating of perceived exertion and running mechanics in elite distance runners: A double-blinded, randomized study - Balsalobre-Fernandez, C.; Romero-Moraleda, B.; Cupeiro, R.; Peinado, A. B.; Butragueño, J.; Benito, P. J. (PLOS ONE, 2018)
Nitrate-rich beetroot juice supplementation has been extensively used to increase exercise economy in different populations. However, its use in elite distance runners, and its potential effects on biomechanical aspects of running have not been properly investigated. This study aims to analyze the potential effects of 15 days of beetroot juice supplementation on physiological, psychological and biomechanical variables in elite runners. Methods: Twelve elite middle and long-distance runners (age = 26.3 ± 5.1yrs, VO2Max = 71.8±5.2 ml*kg-1*min-1) completed an incremental running test to exhaustion on a treadmill before and after a 15-days supplementation period, in which half of the group (EG) consumed a daily nitrate-rich beetroot juice and the other group (PG) consumed a placebo drink. Time to exhaustion (TEx), running economy, vastus lateralis oxygen saturation (SmO2), leg stiffness and rate of perceived exertion (RPE) were measured at 15, 17.1 and 20 km/h during the incremental test. Results: Likely to very likely improvements in EG were observed for the RPE (Standardized mean difference (SMD) = -2.17, 90%CI = -3.23, -1.1), SmO2 (SMD = 0.72, 90%CI = 0.03, 1.41) and TEx (SMD = 1.18, 90%CI = -0.14, 2.5) in comparison with PG. No other physiological or biomechanical variable showed substantial improvements after the supplementation period. Conclusions: Fifteen days of nitrate-rich beetroot juice supplementation produced substantial improvements in the time to exhaustion in elite runners; however, it didn`t produce meaningful improvements in running economy, VO2Max or mechanical parameters.